Seasonal variation of Alphitobius diaperinus population in broiler facilities in the center-north region of the state of São Paulo - Camargo Neto, AF; Tallarico, E; Capriogli, MA; Soares, VE; Meireles, Marcelo Vasconcelos [UNESP]; Silva, GS (Fundação APINCO de Ciência e Tecnologia Avícolas, 2006)
The seasonality of Alphitobius diaperinus population was studied during different seasons during one year, in broiler facilities located in the center-north region of the State of São Paulo. Parasite counting was weekly carried out by the use of traps adapted from the modified model of Arends. During the experimental period, facilities were not submitted to chemical treatment, and the litter was changed between flocks. A lower number of adults and larvae was observed during autumn, with the peak registered in the summer. There was no significant difference between spring and winter averages (adults and larvae), and between spring and summer averages (adults). Average temperatures in the facilities varied from 23.4ºC (winter) to 27.1ºC (spring). The environmentally controlled systems used by the broiler industry provide an adequate habitat for A. diaperinus development. The continuous monitoring of the population of this parasite is essential for designing control strategies, and this can be accomplished by utilizing the traps used in the present experiment.
Keywords: Alphitobius diaperinus; broiler chickens; monitoring; seasonality